FINANCIAL RATIO ANALYSIS AS A TOOL FOR MEASURING FINANCIAL PERFORMANCE IN PT. BATURAJA CEMENT (PERSERO) - Nursella Ramadani; Boris Brahmono; Yogie Surya Danirizka (WORLDVIEW ( Development economic and sharia studies journal ), 2024)
The financial performance of PT Semen Baturaja (Persero) for the period 2020-2022 needs to be evaluated to determine the effectiveness of management in managing the company's finances. The purpose of the study is to measure the financial performance of PT Semen Baturaja (Persero) through financial statement analysis over the period 2020, 2021, and 2022. This study uses various types of financial ratios such as Liquidity, Solvency, and Profitability. The research method used is qualitative with a quantitative approach. The data used is sourced from the financial statements of PT Semen Baturaja (Persero) Tbk for the years 2020, 2021, and 2022, obtained from the Indonesia Stock Exchange. The analysis results show that the company has good liquidity because current assets are higher than current liabilities. The solvency ratio level is quite healthy. Although the Debt to Asset Ratio (DAR) indicates high debt, the low Debt to Equity Ratio (DER) values show that most of the assets are still funded by equity. The company's profitability level is less healthy. Although the Gross Profit Margin (GPM) shows positive results and is higher than the industry average, other ratios such as Operating Profit Margin (OPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) indicate that the company has significant room for improvement in operational efficiency, cost management, and optimization of asset and equity utilization. Keywords: Analysis, Liquidity, Solvency, Profitability